PENGARUH PENDAPATAN DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA PERUSAHAAN SUB SEKTOR SEMEN YANG TERDAFTAR DI BEI - Netty Fiska Giawa; Putu Rani Susanthi (Journal of Innovation Research and Knowledge, 2026)
This research aims to analyze the effect of operating revenue and operating expenses on net income in cement sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2024 period. The research method used is quantitative with a descriptive approach.The results show that operating revenue has a partially positive and significant effect on net income, proven by a significance value of 0.001<0.05. A positive coefficient of 1.095 indicates that every one-unit increase in revenue will increase net income by 1.095 units.In contrast, operating expenses partially have an effect but are not significant on net income, despite having a positive coefficient of 0.210, because the significance value is 0.151>0.05. However, simultaneously, both operating revenue and operating expenses have a significant effect on net income, with a significance value of F=0.001<0.05. The Adjusted R Square value of 0.811 indicates that 81.10% of the variation in net income can be explained by operating revenue and operating expenses while